Direct Carotid Artery Exposure for Acute Cerebral Infarction in Hybrid Angiography Suite: Indications and Limitations - Chen, Ching-Chang; Chen, Chun-Ting; Wu, Yi-Ming; Hsieh, Po-Chuan; Yeap, Mun-Chun; Chang, Chien-Hung; Lin, Chuan-Min; Chen, Shao-Wei (Frontiers in Surgery, 2022)
Abstract Objective: For endovascular intervention of acute ischemic stroke, the transcervical route is an alternative approach in patients with challenging anatomical variations. Percutaneous puncture is a common way, but it can cause many fatal complications. Direct carotid artery exposure is an alternative for reducing complications. We demonstrate a technique of direct carotid exposure in patients in whom transfemoral or transbrachial approaches were impossible. We present patient outcomes and discuss the indications and limitations of this procedure. Methods: We retrospectively reviewed the cases of patients undergoing direct carotid exposure for acute ischemic stroke in a hybrid angiography suite and presented the details of the technique. Results: Among 548 consecutive patients with acute large vessel strokes who were treated by emergency endovascular thrombectomy or stenting between January 2015 and September 2020 in our center, only 8 (1.46%) required a transcervical approach. Of them, 7 underwent direct carotid exposure with successful recanalization and good clinical outcomes. Conclusions: Direct carotid exposure for endovascular stroke treatment is effective and advantageous in patients with challenging anatomical variations. Performing this procedure in carefully selected patients in the hybrid angiography suite can be beneficial in terms of open surgeries, save time, and decrease the risk of postoperative complications.